Beginning Java and Flex : migrating Java, Spring, Hibernate, and Maven developers to Adobe Flex - Di Pisa, Filippo (New York : Apress : Distributed by Springer-Verlag New York, 2009)
"Learn to build powerful enterprise Java applications using Adobe Flash as the presentation layer"--Cover.
Includes index.
Keywords: Flex (Computer file); Java (Computer program language); Cross-platform software development; Internet programming; Web sites -- Design